Well-dispersed cellulose nanofiber in low density polyethylene nanocomposite by liquid-assisted extrusion - Tengku Yasim Anuar, Tengku Arisyah; Ariffin, Hidayah; Norrrahim, Mohd Nor Faiz; Hassan, Mohd Ali; Andou, Yoshito; Tsukegi, Takayuki; Nishida, Haruo (MDPI, 2020)
Two different liquid assisted processing methods: internal melt-blending (IMB) and twin-screw extrusion (TWS) were performed to fabricate polyethylene (PE)/cellulose nanofiber (CNF) nanocomposites. The nanocomposites consisted maleic anhydride-grafted PE (PEgMA) as a compatibilizer, with PE/PEgMA/CNF ratio of 97/3/0.5–5 (wt./wt./wt.), respectively. Morphological analysis exhibited that CNF was well-dispersed in nanocomposites prepared by liquid-assisted TWS. Meanwhile, a randomly oriented and agglomerated CNF was observed in the nanocomposites prepared by liquid-assisted IMB. The nanocomposites obtained from liquid-assisted TWS exhibited the best mechanical properties at 3 wt.% CNF addition with an increment in flexural strength by almost 139%, higher than that of liquid-assisted IMB. Results from this study indicated that liquid feeding of CNF assisted the homogenous dispersion of CNF in PE matrix, and the mechanical properties of the nanocomposites were affected by compounding method due to the CNF dispersion and alignment.